THE EFFECT OF SOCIAL MEDIA MARKETING ON BRAND AWARENESS OF SEJUTA PENGUSAHA - Indry Annisa Azarine; Trisha Gilang Saraswati (Institut Pendidikan Tapanuli Selatan, 2021)
The growth of business community in Indonesia is very fast, currently there are approximately 25 million business community accounts on Instagram. SejutaPengusaha is one of the business communities in Indonesia that not only provides education, but also provides its own e-commerce platform to support its members. The brand awareness of SejutaPengusaha is currently good enough with the number of followers on Instagram as many as 45.600 people, but this number is still far from the expected target. This study was conducted to determine the effect of social media marketing on brand awareness of Sejutapengusaha. This research is included in the type of quantitive research. The sampling technique used is probability sampling of 400 respondents who are Instagram users and know about SejutaPengusaha as a business community. The method in this research is quantitive with descriptive analysis techniques and uses multiple liniear regression analysis. Based on the results of the study, the variable social media marketing has an effect on brand awareness simultaneously by 50,9%, while 49,1% can be explained by other factors outside of this study. Partially, the effect of online communities (X1) on brand awareness (Y) was 7,1%, interaction (X2) was 11,3%, sharing of content (X3) was 1,8%, accessibility (X4) was 12,5%, and credibility (X5) was 18,2%. The suggestion for SejutaPengusaha is to increase two-way interaction on Instagram by creating a question caption that invites answers from followers and optimizing social media InstagramusingAds to increase the level of brand awareness.